Smart Contracts in Islamic Finance: A Content Analysis of Sharia Compliance and Blockchain Applications - Haryani Santo Hartono (Penerbit Hellow Pustaka, 2026)
This paper examines the theoretical embedding and the practical siting of smart contracts in relation to Islamic finance. It uses a qualitative thematic content analysis study to draw conclusions on the ways blockchain-based smart contract system may be incorporated into the values of Sharia using academic resources, regulatory and industry reports of the year 2015 to 2025. The results indicate that smart contracts provide a meaningful opportunity in operational efficiency, where there can be a calculation of zakat based on smart contracts, clear fund management, and financial inclusion with mobile delivery. They have remained difficult nonetheless, especially with regard to reconciling the determinist aspect of code with the codes of the Islamic law which are niyyah (intention), ridaʾ (mutual consent) and ijtihad (contextual reasoning). Regulatory imprecision, the relative lack of input by the Sharia scholars in the formulation of the system and the challenges in encoding complicated Islamic contracts also limit adoption. In spite of the previous standards, like Sharia Standard No. 59 (2023) developed by AAOIFI, there is still a developing structure of jurisprudential and ethical framework. The paper suggests Sharia-by-design, interdisciplinary, real-time Sharia audit, unambiguous regulatory fatwa and mechanisms of dispute resolutions as means of facilitating ethical digital transformation. The findings represent a part of the emerging knowledge base on Islamic fintech, as the basic feature of technological adaptation should be the epistemological and normative correspondence of the practice to Islamic law.